Synthesis, in vivo and in silico analgesic and anti-inflammatory studies of α-D-ribofuranose derivatives - Sabiha Enam Spriha; Fahad Imtiaz Rahman; S. M. Abdur Rahman (Elsevier, 2021)
Five α-D-ribofuranose analogues (2, 3, 4, 5 and 6) were synthesized in good yields from 3-O-benzyl-4-C-(hydroxymethyl)-1, 2-O-isopropylidene-α-D-ribofuranose (1). The synthesized compounds were then subjected to analgesic, anti-inflammatory, antimicrobial and antioxidant assays. Compound 3 demonstrated 79.74% (P < 0.001) writhing inhibition and highest reaction time of 2.55 ± 0.13 min (P < 0.001) after 30 min of oral administration in peripheral and central analgesic assay, respectively, at 50 mg/kg dose. Compound 2 and 6 exhibited significant anti-inflammatory activity at 100 mg/kg dose with paw edema inhibition of 91.15% (P < 0.001) and 95.13% (P < 0.001), respectively, in 4th hour. The synthesized analogues did not show notable antioxidant and antibacterial properties. Molecular docking study revealed higher binding affinity of −8.1 kcal/mol and −8.9 kcal/mol of compound 3 towards cyclooxygenase-1 and phospholipase A2, respectively, compared to −7.7 and −7.6 kcal/mol respectively for corresponding native ligands. Compound 2 demonstrated binding affinity of −9.1 kcal/mol towards interleukin-1 receptor-associated kinase-4 compared to −8.7 kcal/mol of the native ligand. The molecular properties related to drug likeness of compounds were found to be within acceptable range. Synthesized D-ribofuranose analogues demonstrated promising analgesic and anti-inflammatory activities and further development may lead to new potent analgesic and anti-inflammatory agents.